Problems in the Implication of the Word Strategy and Its Application in Translating Poetry: A Contrastive Linguistic Study - SEKHRI, Ouided (Journal of Human Sciences, 2015)
There  is  some  disagreement  about  translation  strategies  in  general  and  the  strategies  used  in  translating  poetry  in  particular  amongst  translation  scholars  not  only  in  the  terminology  but  also  in  the  concept  since  different  labels  such  as  technique,   procedure,  method,  and  strategy  are  utilized.  These  terms  can  generally  overlap  which  confuses  some  concepts  with  the  others.  In  this  respect,  this  study  focuses  on  translation  strategies  which  are  the  ways  that  a  translator  may  follow  when  finding  exact  equivalents  is  almost  impossible.  These  strategies  swing  between  domesticating  the  source  text  to  the  norms  that  govern  the  target  text  and  foreignizing  the  target  text to  the  rules  that  manage  the  source  text. Thus,  distinguishing  between  main  and  secondary  ideas,  establishing  conceptual  relationships,  searching  for  information,  paraphrasing, back  translating,  translating  out  loud,  establishing  an  order  for  documentation, etc.  help  the  translator  find  a  solution  in  order  to  mediate  between  the  source  text  and  the  target  text.  For  that,  since  there  is  no  unified  model  about  the  strategies  used  in  translating  poetry;  we  shall  try  to  find  a  solution  through  analyzing  five  poems  of  Robert  Frost  using  the  method  of  analyzing  literary  texts.